Money and Control: Rebel Groups and the Forcible Recruitment of Child Soldiers. Issue 3 (2nd July 2016) - Faulkner, Christopher M.
ABSTRACT: This article examines the forcible recruitment of child soldiers by rebel organizations through a comparative case study analysis of the National Resistance Army and the Lord's Resistance Army in Uganda. Responses by the international community to the use of children as soldiers have continued to be ineffective, and understanding the factors that not only motivate a group to forcibly recruit but also the factors that dictate their level of forcible recruitment is crucial to curtailing the practice. This article investigates the role that endowments of a rebel group have on their decision to forcibly recruit children as soldiers. Adapting Jeremy Weinstein's theory of the role of initial endowments on rebel group's use of force, I explain why rebel organizations forcibly recruit children. I suggest that the type of endowments matter, specifically the type of endowments accessible to an organization during both its formation and throughout its lifespan. Endowments thus come in two forms—economic and social and each impacts how the group structures control and recruitment practices. The findings demonstrate that groups lacking social endowments will be more likely to disregard the well-being of local populations and engage in violent recruitment tactics. In addition, fluctuations of a group's economic endowments will impact the level of forcible recruitment of children perpetrated by the group.